Cyana barbora, a new species from Sichuan, southwestern China (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Volynkin, Anton V.; Saldaitis, Aidas (Zootaxa, 2020)
The Cyana dohertyi (Elwes, 1890) species-group was erected by Volynkin et al. (2017) and characterized in details by Volynkin et al. (2019). The group is most diverse in mainland China and northern Indochina and comprises 16 valid species and two subspecies (Volynkin et al. 2019; Singh et al. 2020). During a lepidopterological expedition to the northwestern part of China’s Sichuan Province in June and July of 2019, a series of specimens of both sexes of an unidentified Cyana species was collected. The species is closely related to Cyana abiens Fang, 1992 known from the Chinese Shaanxi and Gansu Provinces. However, the specimens collected in Sichuan and C. abiens have conspicuous external and genital differences and the Sichuan population represents another species, which is described below as new.